Geometry of s-space and its using for modeling and optimization complex systems - Kovaluov, Y. N.; Plosky, V. O.; Djyrik, H. V.; Shevel, L. V. (Proceedings of National Aviation University (archive), 2003)
Components of the S-space wave model - axioms, self-organization theory, mappings - are described.The general model “human-environment” and some of the working models are considered. Also contains examples of application of the S-space self-organization theory by optimization of complex technological systems